Constructing ultraviolet nonlinear optical crystals with large second harmonic generation and short absorption edges by using polar tetrahedral S2O3 groups. Issue 9 (14th April 2023) - Ke, Shixian; Fan, Huixin; Lin, Chensheng; Ye, Ning; Luo, Min
Abstract : It is generally considered difficult for traditional sulfates to exhibit strong second harmonic generation (SHG) responses and large birefringence values because SO4 groups are nonpolar tetrahedral structures. Abstract : It is generally considered difficult for traditional sulfates to exhibit strong second harmonic generation (SHG) responses and large birefringence values because SO4 groups are nonpolar tetrahedral structures. However, by theoretical calculations, we found that polar tetrahedral S2 O3 shows great improvements in anisotropy and second order polarizability compared to SO4 while the wide band gap can be preserved. On this basis, a nonlinear optical (NLO) crystal (NH4 )2 S2 O3 with excellent performance was synthesized. As expected, it exhibited a strong SHG response (3.3× that of KDP), suitable birefringence (0.077@546 nm) and a short absorption edge (238 nm). According to the first principles calculations, the polar tetrahedral S2 O3 group is the main source for the SHG response of (NH4 )2 S2 O3 . These findings indicate that the polar S2 O3 group is a kind of NLO functional group with superior comprehensive properties, and has great potential to develop more NLO crystals with superior comprehensive properties.